(untitled) (Mustansiria Dental Journal, 2018)
Background: The purpose of this study was to determine the type of bad oral habits "sucking (thump, index, more than one figure), nail or pencil biting, tongue thrusting, lip sucking" and its relation to age, gender, malocclusions and type of feeding (breast or bottle), in patients above the 6 years of age. Material and methods: 110 patients of oral habit reported to the department of pedodontics and preventive dentistry and department of orthodontics at the collage of dentistry Baghdad University, during a one year period (2005-2006), Thos were 35 male and 75 females in age range between 6- 13 years. Result: Thumb sucking represented the predominate habit (34.55%) for all age groups, The age group that showed the highest oral habit was 8-9 years in which (35.45%) children had oral habit, female children (68.18%) were more than male, the children who sucked their thumb were more likely to develop an increased over jet, while the anterior open bite mostly seen in children with tongue thrust, The children who suck their lip showed deep bite and an increased in the over jet. Conclusions: oral habits had dental effect rather than skeletal effect, there was no association between oral habit and pattern of child’s feeding.